National media policy - Dyal, Rajeshwar; Gupta, V. S. (Published for AMIC, Friedrich Ebert Stiftung by Concept Pub. Co., 1996)
Papers presented at a seminar organized by Asian Mass Communication Research and Information Center (AMIC).